2011
DOI: 10.1088/0957-4484/22/9/095707
|View full text |Cite
|
Sign up to set email alerts
|

Processive behaviour of kinesin observed using micro-fabricated cantilevers

Abstract: The mechanical characterization of biomolecular motors requires force sensors with sub-piconewton resolution. The coupling of a nanoscale motor to this type of microscale sensors introduces structural deformations in the motor according to the thermally activated degrees of freedom of the sensor. At present, no simple solution is available to reduce these effects. Here, we exploit the advantages of micro-fabricated cantilevers to produce a force sensor with essentially one degree of freedom and a spring consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Preparation and Enzymatic Digestion of MicrotubulesPaclitaxel-stabilized Cy5-or rhodamine-labeled and unlabeled MTs were prepared basically as described previously (29) except that no biotinylated tubulin was used. Paclitaxel-free Cy5-labeled MTs were digested with 200 g/ml subtilisin type XXIV (Sigma) for 20 min at 37°C and stabilized by the addition of Paclitaxel before the digestion was terminated with 2 mM 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride (AppliChem).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation and Enzymatic Digestion of MicrotubulesPaclitaxel-stabilized Cy5-or rhodamine-labeled and unlabeled MTs were prepared basically as described previously (29) except that no biotinylated tubulin was used. Paclitaxel-free Cy5-labeled MTs were digested with 200 g/ml subtilisin type XXIV (Sigma) for 20 min at 37°C and stabilized by the addition of Paclitaxel before the digestion was terminated with 2 mM 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride (AppliChem).…”
Section: Methodsmentioning
confidence: 99%
“…First, in control experiments, it was observed that addition of buffer or a control protein, a recombinant form of Plasmodium falciparum lactate dehydrogenase, to the experimental chamber did not produce any observable changes in the position of the contact point or in the adhesion force. However, in Mx strain MX2 cells, the addition of a truncated fragment of Fn (FnIII [12][13][14] ) that binds the UspA1 head region (see below) resulted in an increase in the distance the bacterium needed to be moved in order to establish contact with the cantilever by 7 AE 5 nm (standard deviation of the mean, SDM), and a complete loss of adhesion force in 90% of contacts. These results indicate that Fn-specific binding to UspA1 can be detected by the LMFM.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of UspA1 at the outer Mx surface were tested using a newly developed LMFM, described in ref. 13. The spring constant of the cantilevers used in this study was 2.4 pN∕nm AE 15% and the cross-section was 1 μm AE 10%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the stalk adopts a contracted conformation, even in its activated state. The stalk has been found to allow free rotation of the cargo relative to the microtubule [39], but stalk rotation is not necessary for motility [25,44]. The compliance of the stalk due to the hinge domains must be essential in allowing kinesin to navigate through the crowded interior of a cell and for many motors to work cooperatively without interfering with each other [40,41].…”
Section: Tailmentioning
confidence: 99%